Aspectos da constituição identitária discente em uma licenciatura na modalidade de EaD - Franco, Ana Maria (2019)
Higher education courses taught in the distance education course have as one of their purposes the expansion of the possibility of training new professionals. With regard to undergraduate degrees, distance education is an opportunity for teacher education. Such training offers both the niche of future professionals who will enter the educational context, as well as lay teachers who want to formalize their classroom experience, in accordance with the legal requirements of professional practice. The creation of PARFOR (National Plan for the Training of Teachers of Basic Education) aims to internalize the formation of graduates in the country, providing means of access to those who may not be able to study in the classroom. Thus, the aforementioned Plan provides access to quality public higher education for both lay teachers in service and for new graduates to enter education and to meet the current shortage of teachers in the country. Our objectives were to analyze how the formation of the language teacher, in an undergraduate degree in Letters, by the Open University of Brazil (UAB), in the PARFOR modality, taken in the distance context, interferes in the identity constitution and representations constituted by the graduated teacher who will act professionally in the presential context. In addition, starting from the reflections on the distance learning context, we also aim to reflect on the issues related to the process of identification of the student, regarding the notion of belonging to the higher education institution. We mobilized, for this work, Austin (1990) reflections on Pragmatics and, above all, Rajagopalan (2003) and Pinto (2012) studies on representation. Regarding identity issues, we mobilized the precepts of Bauman (2005), Hall (2006), Woodward (2007) and Silva (2007). Regarding the studies on distance education, we mainly mobilized the studies of Vidal and Maia (2010), as well as Moore and Kearsley (2013). About teacher training, we mobilized, above all, Moro (2009) and Guilherme (2013). Data collection was done through a semi-structured interview with four participants from a graduation class in Letters/Spanish of PARFOR mode. Although target language is not our focus, the issue of habilitation without proper foreign language proficiency was a constant in the participants' words. In addition, we noticed that most felt only belonging to the course, in the way of identification with face-to-face aspects of graduation, such as: face-to-face support pole or voluntary participation in activities at the physical headquarters of the university that offered the course. Another point that caused us reflections was the question of teacher identity constitution, after attending a distance learning degree. Many participants not only became face-to-face teachers, but also wished to act in the distance context, and even one of the participants after the course became a tutor of an undergraduate degree in a private institution. Keywords: Distance Learning. Teacher training. Identity Formation. Representation.